Analytical Study on Seismic Behaviour of Steel Plate Shear Wall with Different Steel Content and Axial Stress Ratio - Lokesh; Ajay Swaroop (International Journal of Scientific Research in Civil Engineering, 2025)
Every structure can be examined for lateral loads from wind and earthquakes, as well as vertical downward gravity loads from imposed and service loads. Steel Plate Shear Walls (SPSW) have received attention over the past forty years to help buildings, particularly high-rise structures, withstand seismic and wind stresses. The purpose of this work is to investigate how the seismic behavior of SPSWs is affected by regularly planned steel plates and the addition of different patterns of channel-shaped stiffeners. Understanding dynamic analysis and response spectrum solutions for building process plant buildings with steel plate sharing walls under four different conditions is the goal of this dissertation. 1) Shear wall made of plane steel plates 2) Shear Wall Made of Diagonally Stiffened Steel Plate 3) Shear wall made of horizontally stiffened steel plates 4) A shear wall made of vertically stiffened steel plates. In the event of an earthquake, the structure of the process plant is crucial to the continuous functioning of any commercial production system. The analytical findings demonstrate that, in comparison to planar steel plates, stiffened steel plates exhibit less generated yield stress and shear wall deformation rotation. This paper’s primary goal is to: 1) Examine how the structure responds to lateral loads caused by seismic loads on the structure by providing a plane SPSW. 2) To investigate how SPSW behaves when stiffeners are positioned horizontally, vertically, and diagonally. 3) To compare, from an economic perspective, the analysis results of SPSW with those of a traditional bracing system.